The prognostic value of baseline and early variations of peripheral blood inflammatory ratios and their cellular components in patients with metastatic renal cell carcinoma treated with nivolumab: The Δ-Meet-URO analysis - Rebuzzi, Sara Elena; Signori, Alessio; Stellato, Marco; Santini, Daniele; Maruzzo, Marco; De Giorgi, Ugo; Pedrazzoli, Paolo; Galli, Luca; Zucali, Paolo Andrea; Fantinel, Emanuela; Carella, Claudia; Procopio, Giuseppe; et al. (Frontiers in Oncology, 2022)
Background: Treatment choice for metastatic renal cell carcinoma (mRCC) patients is still based on baseline clinical and laboratory factors. Methods: By a pre-specified analysis of the Meet-URO 15 multicentric retrospective study enrolling 571 pretreated mRCC patients receiving nivolumab, baseline and early dynamic variations (Δ) of neutrophil, lymphocyte and platelet absolute cell counts (ACC) and their inflammatory ratios (IR) were evaluated alongside their association with the best disease response, overall (OS) and progression-free survival (PFS). Multivariable analyses on OS and PFS between baseline and Δ ACC and IR values were investigated with receiving operating curves-based cut-offs. Results: The analysis included 422 mRCC patients. Neutrophils-to-lymphocytes ratio (NLR), increased over time due to consistent neutrophils increase (p<0.001). Higher baseline platelets (p=0.044) and lower lymphocytes (p=0.018), increasing neutrophil Δ (p for time-group interaction<0.001), higher baseline IR values (NLR: p=0.012, SII: p=0.003, PLR: p=0.003), increasing NLR and systemic immune-inflammatory index (SII) (i.e., NLR x platelets) Δ (p for interaction time-group = 0.0053 and 0.0435, respectively) were associated with disease progression. OS and PFS were significantly shorter in patients with baseline lower lymphocytes (p<0.001 for both) and higher platelets (p=0.004 and p<0.001, respectively) alongside early neutrophils Δ (p=0.046 and p=0.033, respectively). Early neutrophils and NLR Δ were independent prognostic factors for both OS (p=0.014 and p=0.011, respectively) and PFS (p=0.023 and p=0.001, respectively), alongside baseline NLR (p<0.001 for both) and other known prognostic variables. Conclusions: Early neutrophils and NLR Δ may represent new dynamic prognostic factors with clinical utility for on-treatment decisions.